Relationship Among Ethical Leadership, Ethical Climate, and Service-Oriented Organizational Citizenship Behavior in the Hospitality Industry - Patti Betina E. Chan; Maria Joan P. Barlis (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
Business ethics has been cited as one of the hospitality industry’s most important issues by many practitioners and academics. Yet, further study on business ethics in the industry has been advised. The purpose of this study was to evaluate the relationship among ethical leadership, ethical climate, and service-oriented OCBs. It investigated whether or not ethical leadership and ethical climate has a substantial impact on service-oriented OCBs, in an Asian country such as the Philippines. The current study discovered that ethical leadership is significantly and positively associated with both service-oriented OCBs and ethical climate. There was also a strong positive association between ethical climate and service-oriented OCBs. The present research can help hospitality organizations cultivate ethical leadership, strengthen an ethical climate, and encourage service-oriented OCBs. Based on these analyses, academics and scholards would benefit from having a deeper understanding of the relationship between ethical leadership, ethical climate, and service-oriented OCBs.